2020
DOI: 10.1051/epjconf/202023701006
|View full text |Cite
|
Sign up to set email alerts
|

ESA’s Lidar Missions Aeolus and EarthCARE

Abstract: ESAs Earth Explorer Aeolus was launched in August 2018. Aboard the first spaceborne wind lidar ALADIN (Atmospheric LAser Doppler INstrument) was switched on in early September 2018 and demonstrated the capability to provide atmospheric wind profiles globally from particle and molecular backscatter. In doing so, it will contribute to the improvement in numerical weather prediction (NWP) and the understanding of global dynamics. At the same, it is a major step for powerful and frequency stabilized ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Absorbing aerosols originating from north China resulted in relatively large LRs at high altitude in Shanghai. Liu et al (2012) reported that vast majority of aerosol particles in the Yangtze Delta region (including Shanghai) were below 2 km. In order to precisely analyze the variation characteristics of the LR in Shanghai, Fig.…”
Section: Temporal Variations In Lrmentioning
confidence: 99%
“…Absorbing aerosols originating from north China resulted in relatively large LRs at high altitude in Shanghai. Liu et al (2012) reported that vast majority of aerosol particles in the Yangtze Delta region (including Shanghai) were below 2 km. In order to precisely analyze the variation characteristics of the LR in Shanghai, Fig.…”
Section: Temporal Variations In Lrmentioning
confidence: 99%
“…First results of the Aeolus instrument characterization and calibration are presented in [1] and [2]. This paper shows first results of the Aeolus Level 2 product assessment.…”
Section: Resultsmentioning
confidence: 96%
“…Global measurements of tropospheric wind, water vapor, CO2, temperature, and surface vegetation from space lidars will be highly desired (Baker et al, 2014; National Academics of Sciences, 2018a; National Academics of Sciences, 2018b), but there are challenges to overcome. ESA's Aeolus wind satellite was launched on August 22, 2018 and demonstrated the feasibility to measure wind from the space (Kanitz et al, 2020). Its fixed-beam pointing cannot provide wind speed and direction, however.…”
Section: Space-based Lidar For Measurements Beyond Aerosol Clouds Amentioning
confidence: 99%
“…A variety of lidar technologies have been developed to provide atmospheric and surface properties during the last 60 years (Fiocco and Smullin, 1963;Weitkamp, 2005;Kashani et al, 2015) to support advancements in digital models of terrain, cryospheric discovery, terrestrial ecology, hydrology, atmospheric science, and oceanography. The successful lidar operations of NASA's Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO, Winker et al, 2010) and Ice, Cloud, and land Elevation Satellite (ICESat, Markus et al, 2017) and ESA's Aeolus wind satellite (Kanitz et al, 2020) highlight a new era of lidar developments and applications. Measurement concepts and technology are evolving simultaneously in different directions.…”
Section: Introductionmentioning
confidence: 99%